Synthesis, bioconjugation and stability studies of [18F]ethenesulfonyl fluoride. (12th July 2018) - Zhang, Bo; Pascali, Giancarlo; Wyatt, Naomi; Matesic, Lidia; Klenner, Mitchell A.; Sia, Tiffany R.; Guastella, Adam J.; Massi, Massimiliano; Robinson, Andrea J.; Fraser, Benjamin H.
Abstract : Fluorine‐18 labelled prosthetic groups (PGs) are often necessary for radiolabelling sensitive biological molecules such as peptides and proteins. Several shortcomings, however, often diminish the final yield of radiotracer. In an attempt to provide higher yielding and operationally efficient tools for radiolabelling biological molecules, we describe herein the first radiochemical synthesis of [ 18 F]ethenesulfonyl fluoride ([ 18 F]ESF) and its Michael conjugation with amino acids and proteins. The synthesis of [ 18 F]ESF was optimised using a microfluidic reactor under both carrier‐added (c.a.) and no‐carrier‐added (n.c.a.) conditions, affording, in a straightforward procedure, 30‐50% radiochemical yield (RCY) for c.a. [ 18 F]ESF and 60‐70% RCY for n.c.a. [ 18 F]ESF. The conjugation reactions were performed at room temperature using 10 mg/mL precursor in aqueous/organic solvent mixtures for 15 min. The radiochemical stability of the final conjugates was evaluated in injectable formulation and rat serum, and resulted strongly substrate dependent and generally poor in rat serum. Therefore, in this work we have optimised a straightforward synthesis of [ 18 F]ESF and its Michael conjugation with model compounds, without requiring chromatographic purification. However, given the general low stability of the final products, further studies will be required for improving conjugate stability, before assessing the use of this PG for PET imaging. Abstract : We report herein the radiosynthesis of [ 18 F]ethenesulfonyl fluoride ([ 18 F]ESF), that proceeds straightforwardly without the need of chromatographic purification. We then investigated the use of [ 18 F]ESF as a new prosthetic group on amino acids, insulin and BSA. While the conjugation methodology and the purification processes were simple and efficient, the stabilities of the final products are strongly substrate‐dependent, and generally low in serum.